Seismic amplitude analysis and rock physics modeling of a geothermal sandstone reservoir in the southern part of the Danish Basin. (January 2021) - Bredesen, Kenneth; Rasmussen, Rasmus; Mathiesen, Anders; Nielsen, Lars Henrik
Highlights: Rock physics feasibility study of the geothermal Bunter sandstone reservoir. Seismic modeling of varying porosity and lithology in a geothermal reservoir. Porosity and permeability estimates from post-stack inversion results. Seismic reservoir characterization in early exploration to reduce pre-drill risks. Adopting exploration tools from the hydrocarbon industry for geothermal purposes. Abstract: We present a rock physics feasibility study to predict the seismic response for various geothermal reservoir scenarios and perform a post-stack seismic inversion, focusing on a sandstone reservoir in south Denmark. Our objective is to investigate how reservoir variations influence the seismic characteristics, and, estimate a spatial porosity and permeability model. The study shows the seismic sensitivity with varying porosity and lithology in the Bunter sandstone, and porosity and permeability estimations away from well locations. The reservoir prognosis was influenced by inherent uncertainties associated with limited local and regional geophysical data.